Ultrastructure of acetylcholine receptor aggregates parallels mechanisms of aggregation - Lee Lara K; Kunkel Dennis D; Stollberg Jes (BMC Neuroscience, 2001)
Abstract Background Acetylcholine receptors become aggregated at the developing neuromuscular synapse shortly after contact by a motorneuron in one of the earliest manifestations of synaptic development. While a major physiological signal for receptor aggregation (agrin) is known, the mechanism(s) by which muscle cells respond to this and other stimuli have yet to be worked out in detail. The question of mechanism is addressed in the present study via a quantitative examination of ultrastructural receptor arrangement within aggregates. Results In receptor rich cell membranes resulting from stimulation by agrin or laminin, or in control membrane showing spontaneous receptor aggregation, receptors were found to be closer to neighboring receptors than would be expected at random. This indicates that aggregation proceeds heterogeneously: nanoaggregates, too small for detection in the light microscope, underlie developing microaggregates of receptors in all three cases. In contrast, the structural arrangement of receptors within nanoaggregates was found to depend on the aggregation stimulus. In laminin induced nanoaggregates receptors were found to be arranged in an unstructured manner, in contrast to the hexagonal array of about 10 nm spacing found for agrin induced nanoaggregates. Spontaneous aggregates displayed an intermediate amount of order, and this was found to be due to two distinct population of nanoaggregates. Conclusions The observations support earlier studies indicating that mechanisms by which agrin and laminin-1 induced receptor aggregates form are distinct and, for the first time, relate mechanisms underlying spontaneous aggregate formation to aggregate structure.